Catastrophe et anabase chez Dulce Maria Cardoso - Maria Araújo da Silva (Catalonia)
In the novel O Retorno (2011), the Portuguese writer Dulce Maria Cardoso develops a deep reflection on the decolonization of Portuguese Africa and the massive repatriation of colonial residents (“retornados”), prompting us to think about the exilic condition and the borders between identity and otherness. While conducting an inquiry about the violence of separation, she shows us that human beings can recover from the catastrophe and consider new horizons, despite injuries and loss.